Financial Performance, Abnormal Return, And External Factor On The Share Price Of Service Companies Before And After The Acquisition At IDX - Setiawan, Chandra; Maulana, Alfan (President University, 2024)
The COVID-19 pandemic is a new challenge for all levels of society worldwide, especially for businessowners whose businesses are affected by government policies to suppress the spread of COVID-19.Therefore, expanding is one of the company's strategies for maintaining its business amid these criticalconditions. In this study, there are two objectives where the first topic aims to find out whether there is adifference in financial performance and abnormal returns before and after the company acquires, and thesecond objective is to find out whether there is an effect of financial performance, inflation, and interestrates on the company's stock price. The results of this study on the first topic show that CR, ROA, ROE,TATO, DER, and Abnormal Return do not have significant differences before and after the companyacquires. The results of the study on the second topic show that CR, ROA, ROE, and inflation have asignificant positive effect on changes in the company's stock price. In contrast, TATO, DER, and interestrates significantly negatively affect changes in the company's stock price.Keywords: COVID-19, Financial Performance, Inflation, Interest Rate,